An approach to sustainable agriculture by untangling the fate of contrasting nitrogen sources in double‐season rice grown with and without biochar. Issue 3 (24th December 2020) - Ullah, Saif; Ali, Izhar; Liang, He; Zhao, Quan; Wei, Shanqing; Muhammad, Ihsan; Huang, Min; Amanullah,; Ali, Nawab; Jiang, Ligeng
Abstract: Excessive use of inorganic nitrogen (N) fertilizers is the primary anthropogenic cause of low N use efficiency and environmental damage in wetland rice agriculture. However, little is known about the performance of traditional inorganic N sources used in paddy rice production. Biochar (BC) is considered to be a climate change mitigation tool that can enhance N uptake and utilization in N‐fertilized crops. To test this hypothesis, we performed a pot experiment to study the fate of 15 N‐labeled urea, ammonium nitrate, and ammonium sulfate with and without BC at tillering, heading, and maturity stages of rice in the early and late seasons of 2019. Fertilizer N leaching was significantly reduced by 75.69% and 110.32% in BC vs. non‐BC treatments across growth stages in the early and late seasons. The rate of leaching was lower for urea than for ammonium nitrate and ammonium sulfate. Furthermore, the addition of BC resulted in 55.58% and 41.33% higher soil 15 N concentrations in the early and late season, respectively, indicating that BC increased N adsorption. 15 N uptake by roots, stems, leaves, panicles, and grains averaged 52.39%, 37.14%, 40.86%, 36.37%, and 29.94% higher in BC‐amended pots than in BC‐free pots in both seasons. There were significant differences ( p  < 0.05) among N sources in terms of fertilizer N loss, residual N, and N uptake, and performance was ranked in the order urea > ammonium sulfate > ammonium nitrate. Overall, our results indicate that urea with BC is a preferable N source for double rice cropping systems compared with ammonium nitrate and ammonium sulfate. Abstract : The management of nitrogen has now been identified as the most imperative dimension for handling the global climate change and soil fertility. By monitoring fertilizer nitrogen dynamics, a pot cultivation experiment was conducted to elucidate how different nitrogen fertilizer sources (urea, ammonium nitrate and ammonium sulfate) with and without biochar alter the ability of the paddy soil to store and cycle these nutrients. Specific analyses included 15‐N leaching, retention and uptake by plant. In this investigation, an obvious differences were recorded among N fertilizers applied with and without biochar and graded in order urea > ammonium sulfate > ammonium nitrate.